Engine Performance Analysis Using Biodiesel from Giant Palm as a Blending Agent - Busari, Rasheed Amao; Fadeyibi, Adeshina; Adebayo, Raheef Kehinde (International Journal of Oil Palm, 2024)
The continuous reliance on petroleum diesel, coupled with growing concerns about environmental degradation, has propelled the exploration of renewable diesel fuel alternatives. This research study delved into the production of giant palm methyl ester through transesterification, employed potassium hydroxide as a catalyst. This alternative fuel was then tested in a single-cylinder, direct injection diesel engine commonly used in Nigeria's agricultural sector, where the demand for sustainable energy solutions is crucial. Pure vegetable oils encounter operational challenges in diesel engines due to their high viscosity, low calorific value, and polyunsaturated nature. Transesterification emerges as a more effective method to modify these properties. Comparisons between the physicochemical parameters of Giant palm methyl ester and convectional diesel fuel revealed significant differences. The calorific value of the produced biodiesel stood at 38,470 MJ/kg, slightly lower than pure diesel's 42.00 MJ/kg. Additionally, the kinematic viscosity of the biodiesel was measured at 10.9 mm2/s. The study also scrutinized engine performance using various biodiesel blends and compared them with conventional diesel. The findings demonstrated the viability of using biodiesel derived from giant palm seed oil in compression ignition engines as a practical alternative to diesel fuel. Lower blends, particularly B5 to B25, adhered closely to ASTM standards, signifying their acceptability. However, as biodiesel concentration increased, both break thermal efficiency and fuel consumption experienced an upward trend. The results showed that the use of biodiesel produced from giant palm seed oil in compression ignition engines is a viable alternative to diesel fuel.